2013
DOI: 10.1016/j.jtcvs.2012.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the incidence and impact of postoperative prolonged alveolar air leak after pulmonary resection

Abstract: PAAL leads to longer hospital stays, and approximately 4.8% of patients undergoing pulmonary resection experience PAAL that necessitates placement of additional chest drains, bronchoscopy, reoperation, or life support. Further study is required to assess the cost-effectiveness of measures to reduce PAAL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 19 publications
(37 reference statements)
6
65
1
1
Order By: Relevance
“…Previous studies have found that the impact of PAL on the healthcare system is significant as it prolongs hospital stay by 4 to 13 days [8] [9] [16] and as a result increases health-care costs [17]. The mean LOS for patients with PAL in our study was significantly longer at 12.6 days compared to 5.0 days for patients in the control group (P < 0.0001).…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…Previous studies have found that the impact of PAL on the healthcare system is significant as it prolongs hospital stay by 4 to 13 days [8] [9] [16] and as a result increases health-care costs [17]. The mean LOS for patients with PAL in our study was significantly longer at 12.6 days compared to 5.0 days for patients in the control group (P < 0.0001).…”
Section: Discussionmentioning
confidence: 44%
“…The definition of a prolonged air leak (PAL) varies in the literature, but the currently accepted definition is an air leak lasting 5 or more days postoperatively [2] which is the average length of stay (LOS) in hospital following lobectomy [3]. In previous studies, PAL has been found to occur in up to 26% of patients following lobectomy and lesser pulmonary resections [4] [5] [6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for a PAL include: chronic obstructive pulmonary disease (COPD), bilobectomy, upper lobectomy, diffusing capacity of carbon monoxide (DLCO) less than 80% predicted and steroid use (3,8). Postoperative air leaks are not just an annoyance that prolongs hospitalization; they can be a surrogate marker for increased morbidity and complications like postoperative atrial fibrillation and pneumonia (9).…”
Section: Apical Spaces and Pals After A Pulmonary Resectionmentioning
confidence: 99%